ASSESSING THE EFFECT OF ORAL HEALTH STATUS AMONG THE VARIOUS BREEDS OF GOATS IN TAMILNADU, INDIA – A CROSS-SECTIONAL SURVEY - Elakiya S; Raj Mohan M; Bharathwaj V V; Sindhu R; Dinesh Dhamodhar; Prabu D; Gousalya V (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The aim is to evaluate the association of oral health status among various breeds of goats. A total of 120 goats were recruited for the cross-sectional study from the blue cross of Tamilnadu and various veterinary colleges based on a simple random sampling method. The oral health status of goats was recorded using the DMFT index, plaque index, tooth erosion index, gingival index, tooth mobility index, and tooth wearing index. The data is collected and tabulated using chi-square. P-value < 0.05 was considered to be statistically significant. In the present study, gingivitis, calculus, plaque, recession, and malocclusion are the other findings found about the oral health status of various breeds of goats. The overall percentage of gingivitis in goats is 40%, and there is no statistically significant relationship between the various breeds of goats. There was statistically significant relation was found between trauma (0.02) and attrition (0.03) among various breeds of goat. The study concluded that while comparing with various breeds of goat, it has a strong impact on oral health status such as trauma and attrition.